2001
DOI: 10.1002/1099-0682(200102)2001:2<471::aid-ejic471>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

Iron(III) Complexation by New Aminocarboxylate Chelators − Thermodynamic and Kinetic Studies

Abstract: The complexation of FeIII by new tetradentate and pentadentate aminocarboxylate chelators, designed to protect cells against iron‐catalysed oxidative damage, was investigated. Ferric iron complexes of N,N′‐bis(3,4,5‐trimethoxybenzyl)ethylenediamine‐N,N′‐diacetic acid (L1), N,N′‐dibenzylethylenediamine‐N,N′‐diacetic acid (L2) and [N‐(2‐hydroxybenzyl)‐N′‐benzylethylenediamine‐N,N′‐diacetic acid] (L3) have been characterized in aqueous solution by potentiometric, UV/Vis spectrophotometric and cyclic voltammetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
14
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 24 publications
3
14
0
Order By: Relevance
“…H 2 O 2 and a reductant, metal complexes like 14 are hydroxylated and their iron affinity increases. In addition to an increase in affinity, another consequence of the added phenolate donor is a decrease in Fe 3+ /Fe 2+ redox potential that prevents further redox cycling of iron 55. The early compounds were not efficient at protecting cells from oxidative stress, probably because they were unable to cross cell membranes.…”
Section: Prochelators For Triggered Activation Against Oxidative Stressmentioning
confidence: 99%
“…H 2 O 2 and a reductant, metal complexes like 14 are hydroxylated and their iron affinity increases. In addition to an increase in affinity, another consequence of the added phenolate donor is a decrease in Fe 3+ /Fe 2+ redox potential that prevents further redox cycling of iron 55. The early compounds were not efficient at protecting cells from oxidative stress, probably because they were unable to cross cell membranes.…”
Section: Prochelators For Triggered Activation Against Oxidative Stressmentioning
confidence: 99%
“…A prerequisite is that the speciation in the aqueous Fe(III)-ligand system is thoroughly characterized in order to establish reliable IR spectra-structure relationships. The Fe(III)MIDA [30] and Fe(III)EDDA [31] systems have been previously studied, and the stability constants determined were used to generate the distribution diagrams displayed in Fig. 4.…”
Section: Atr-ftir Spectroscopic Characterization Of Surface Complexesmentioning
confidence: 99%
“…The stability constants used to generate the MIDA diagram are from Sanchiz et al[30] and the EDDA diagram from Serratrice et al[31].…”
mentioning
confidence: 99%
“…Lipophilic enterobactin analogues (tris-catecholates) have been described ) using a spermidine spacer in which the N terminal nitrogen atom is substituted by long alkyl chains. Lipophilic chelators derived from EDTA (Galey et al 2000;Serratrice et al 2001) or trisaminophenol (Bollinger et al 1995) have also been reported. An elegant strategy has been developed by Shanzer and collaborators in which the lipophilic ferrichrome analogues with masked hydrophilic moieties (Figure 8a) A series of three tris-hydroxyquinolinate derivatives of O-TRENSOX containing a C-pivotal atom as spacer and grafted with various polyoxyethylene chains (POE) has been prepared in our group (Figure 9a, Imbert et al 2002), leading to the observation that the hydrophilic-lipophilic balance (quantified by the partition coefficients) of the overall neutral ferric complexes is tuned by the length of the polyoxyethylene chain.…”
Section: Lipophilic and Amphiphilic Siderophoresmentioning
confidence: 99%